تأثير تراكم الرسوبيات على انخفاض المخزون الحي في بحيرة سد 16 تشرين - حسن عزالدين; حماد منذر; حواط ماهر (Latakia University Journal -Engineering Sciences Series, 2018)
This study aims to find out the amount of sediments accumulated in the lake of 16 October dam since the start of investing dam until now, and knowledge wastage in the useful storage of dam as the result of these sediments accumulated, and thus suggest appropriate solutions to remove these sediments in order to prolong the investment useful life of dam. For this purpose the amount of transported sediment to the reservoir during the flood was measured, and samples were taken from the sediment to know their particular analysis and thus to know the nature of them , and has to take advantage of the topographic survey of the reservoir to know the bathymetry changes of reservoir. As a result of this study, the amount of accumulated sediments in the dam’s lake was estimated to be 4640000 tons during the investment period. These sediments caused a loss of useful storage volume of 9.1 million cubic meters, or about 7.58% of the total useful volume of the dam, Which requires the removal of sediments in dry years or by discharging them through the lower outlets of the dam. تهدف هذه الدراسة إلى معرفة كمية الرسوبيات المتجمعة في بحيرة سد 16 تشرين منذ البدء باستثمار السد حتى الآن, ومعرفة الفاقد في حجم التخزين المفيد للسد نتيجة هذه الرسوبيات المتجمعة, وبالتالي اقتراح الحلول المناسبة للتخلص من هذه الرسوبيات بهدف إطالة العمر الاستثماري المفيد للسد. من أجل هذا الهدف تم قياس كمية الرواسب المنقولة للبحيرة خلال الفيضان, كما تم أخذ عينات من هذه المواد المترسبة لمعرفة تركيبها الحبي وبالتالي معرفة طبيعة هذه الرواسب, كما تمت الاستفادة من المسح الطبوغرافي لبحيرة السد لمعرفة التغيرات الحاصلة في أعماق البحيرة. وبنتيجة هذه الدراسة تبين أن كمية الرسوبيات المتجمعة في بحيرة السد تعادل 4640000 طن خلال فترة الاستثمار, حيث تسبب هذه الرسوبيات خسارة في حجم التخزين المفيد مقداره 9.1 مليون متر مكعب أي حوالي 7.58% من الحجم الإجمالي المفيد للسد, الأمر الذي يتطلب إجراء عمليات تعزيل للرسوبيات في السنوات الجافة أو عن طريق تصريفها من خلال المخارج السفلية للسد.